Analysis of pedagogical political projects school in Teofilo Otoni city under the strategic planning view (Research, Society and Development, 2019)
The Pedagogical Political Project or Political Pedagogical Proposal (PPP) is a guiding document of the work of every teaching institution, since it represents the unification of decisions built collectively with the school community, in favor of education. Thus, this document can be elaborated through a strategic planning, which is presented as a form of organization of great importance, for the adequate development of this teaching-learning process, because the future perception about the objectives outlined and the decision making allow the monitoring of results and meeting expectations. In this way, the present study presents the Strategic Planning as a managerial tool that facilitates the process of conducting the PPP, and consequently in the execution of its proposals, in the construction context. From the study and analysis of the PPP's of the city of TeófiloOtoni / MG, it was possible to observe that educational institutions could better structure their projects, according to the pertinent legislations, thinking about their future actions of PPP construction in the planning context strategic.